Penaksiran Riap Biomassa dan Riap Karbon pada Famili Sapindaceae di Kebun Raya Purwodadi (Biomass and Carbon Increments of Sapindaceae Family in Purwodadi Botanic Garden) - Danarto, Setyawan Agung (Jurnal Sylva Lestari, 2020)
Global warming has adverse effects on human life, which can be prevented by planting many trees. Sapindaceae family has various purposes, particularly as fruit producers. However, research on the potential of the Sapindaceae family as a carbon sequester is still lacking. This study aimed to determine the annual increment of biomass and carbon absorption of 22 species from the Sapindaceae family in Purwodadi Botanic Garden. Data were collected using a non-destructive method in the Purwodadi Botanic Garden in July-September 2019. The research tool used in this research included stationery, roll meter, and tally sheet. Biomass was measured with the Kettering equation. The results revealed variations in the value of biomass and the carbon increment of each species. Three species of the Sapindaceae family that have biomass and high carbon increment were Litchi chinensis, Filicium decipiens, and Schleichera oleosa. Keywords: biomass increment, carbon increment, global warming, sapindaceae family